Tuning the Curie temperature of Fe90Sc10 nanoglasses by varying the volume fraction and the composition of the interfaces. (15th January 2019) - Wang, Chaomin; Mu, Xiaoke; Chellali, Mohammed Reda; Kilmametov, Askar; Ivanisenko, Yulia; Gleiter, Herbert; Hahn, Horst
Abstract: Fe90 Sc10 nanoglass was produced by consolidating Fe90 Sc10 glassy nanoparticles (GNp) into bulk solid material. The average diameters of the GNp, which were produced by inert gas condensation, decreased as He pressure decreased. The volume fraction of the interfaces within the nanoglass increased as the diameters of the primary GNp decreased. The segregation of the Fe atoms at the surfaces of the GNp varied, so the composition of the interfaces was different. As the Curie temperature of Fe90 Sc10 nanoglass is primarily dependent on the volume fraction and the composition of the interfaces, the Curie temperature increased as He pressure decreased. Graphical abstract: Unlabelled Image